Severe Scabies: A French Multi-centre Study Involving 95 Patients with Crusted and Profuse Disease and Review of the Literature - Charbel Skayem; Askour Majda; Charlotte Gary; Francois Hemery; Emmanuel Mahé; Frederic Caux; Nicolas Dupin; Patricia Senet; Alix Greder-Belan; Brigitte Hillion; Cecile Meni; Philippe Saiag; et al. (Medical Journals Sweden, 2023)
The aim of this multi-centre French retrospective study was to identify severe, i.e. crusted and profuse, scabies patients. Records were retrieved from 22 Dermatology or Infectious Diseases departments in the Ile-de-France from January 2009 to January 2015 to characterize epidemiology, demography, diagnosis, contributing factors, treatment features, and outcomes in severe scabies. A total of 95 inpatients (57 crusted and 38 profuse) were included. A higher number of cases was observed among elderly patients (>75 years), mostly living in institutions. Thirteen patients (13.6%) reported a history of previously treated scabies. Sixty-three patients (66.3%) had been seen by a previous practitioner for the current episode (up to 8 previous visits). Initial misdiagnosis (e.g. eczema, prurigo, drug-related eruptions, psoriasis) was documented in 41 patients (43.1%). Fifty-eight patients (61%) had already received 1 or more previous treatments for their current episode. Forty percent received corticosteroids or acitretin for an initial diagnosis of eczema or psoriasis. Median time from the onset of symptoms to the diagnosis of severe scabies was 3 months (range 0.3-22). Itch was present in all patients at diagnosis. Most patients (n=84, 88.4%) had comorbidities. Diagnostic and therapeutic approaches varied. Complications occurred in 11.5% of cases. To date, there is no consensus for diagnosis and treatment, and future standardization of is required for optimal management.